1987
DOI: 10.1111/j.1399-6576.1987.tb02522.x
|View full text |Cite
|
Sign up to set email alerts
|

Propofol vs thiopentone as anaesthetic agents for short operative procedures

Abstract: In a randomized open study, 120 healthy female patients were included. For short gynaecological procedures they were anaesthetized with either propofol 2.5 mg X kg-1 (n = 60) or thiopentone 5 mg X kg-1 (n = 60) in combination with nitrous oxide/oxygen (67%/33%). Supplementary doses of propofol (10-20 mg) or thiopentone (25-50 mg) were given when necessary during the procedure. Induction characteristics for propofol and thiopentone 1 min after start of induction were similar. Propofol seemed to have a more depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 11 publications
(7 reference statements)
0
18
1
Order By: Relevance
“…Since we did not measure the blood concentrations of the anesthetics, it is not certain whether the doses used here produced plasma concentrations that would be clinically relevant. Furthermore, in clinical practice, the optimal dose of thiopental for induction of anesthesia is generally accepted to be 1.6 to two times larger than that of propofol [1,3]. Therefore, we should note that, in our experimental design, we did not compare the two drugs at equipotent doses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since we did not measure the blood concentrations of the anesthetics, it is not certain whether the doses used here produced plasma concentrations that would be clinically relevant. Furthermore, in clinical practice, the optimal dose of thiopental for induction of anesthesia is generally accepted to be 1.6 to two times larger than that of propofol [1,3]. Therefore, we should note that, in our experimental design, we did not compare the two drugs at equipotent doses.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of anesthesia with propofol is generally associated with decreases in arterial blood pressure and minimal change in heart rate [1][2][3]. Propofol decreased myocardial contractile force in humans [4], in isolated mammalian hearts [5,6], and in chronically instrumented dogs [7], suggesting that the negative inotropic effect of propofol contributes to the decreases in arterial blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…It is, however, difficult to find a small difference when the negative inotropic effects of propofol at the doses used in the ventricle were much less than those in the atrium. On the other hand, the optimal dose of thiopental for induction of anesthesia is generally accepted to be 1.6 to 2 times larger than that of propofol [2,15]. Therefore, we can conclude that the negative inotropic effect of propofol is less prominent than that of thiopental at anesthetic induction doses.…”
mentioning
confidence: 75%
“…ventricular tachycardia. 11, 13 Singh et al found that in patients with left ventricular dysfunction, there was a significant decrease from the baseline in the heart rate, mean arterial pressure after induction in all three groups of patients. The thiopentone group recorded the least decrease in heart rate (-7%), while the maximum decrease was seen in the midazolam group (-15%).…”
Section: Discussionmentioning
confidence: 99%
“…9 The incidence of pain on injection was significantly greater following propofol than after thiopentone and midazolam which was in consistent with previous findings. 5, 13 Shah PJ et al found that 20% of patients complained of pain on injection and 3.33% patients had thrombophlebitis with propofol compared 0% with thiopentone and midazolam. 4 Rahman MH et al found that 14% of 5 Suri Y found that no patients with either thiopentone or midazolam experienced any venous intolerance.…”
Section: Discussionmentioning
confidence: 99%